Agents Celebrating and Registering Official Marriages and Issuing Marriage Certificates in Brazil and France: A Comparative-Terminological Study (Revista de Estudos da Linguagem, 2024)
In this paper, it is aimed to carry out a comparative-terminological study on the terms designating the agents involved in the celebration and registration of official marriages and in the issuance of marriage certificates in Brazil and France. Thus, it is intended to find the degrees of equivalence that are maintained between these terms, reflecting on the terminological differences and similarities that underlie them. To do so, this study is based on the theoretical and methodological assumptions of Terminology, more specifically on Bilingual Terminology. Therefore, criteria to establish the equivalence degrees between the terminological units studied were adopted according with this approach. As main results, this research reveals that there are more differences than similarities between the terms analyzed in Portuguese from Brazil (PB) and French from France (FF). In this sense, eleven cases of empty equivalence and seven cases of partial equivalence were found. Based on these data, it was observed that, when it was possible to establish an equivalence relation between the studied terms, this equivalence is partial. Furthermore, this study found that most terminological units in BP do not have an equivalent in FF in the domain in question. These particularities are mainly due to legislative differences regarding the way according with the rules of official marriages are organized in these two countries. In turn, these nations are influenced by socio-cultural issues underlying the area of civil law, as that they are two distinct historical and social realities.